"I'll Be Right Behind You": Native American Families, Land Debt, and College Affordability - Amanda R. Tachine; Nolan L. Cabrera (SAGE Publishing, 2021)
Family connections are critical for Native student persistence, yet families' voices are absent in research. Using an Indigenous-specific version of educational debt, land debt, we center familial perspectives by exploring the financial struggles among Native families as their students transition to a Predominately White Institution. Findings indicate that Indigenous families experienced fear and frustration surrounding college affordability and the financial aid process. Regardless, these Native families made extreme sacrifices in paying for college. These findings were contextualized within the economic conditions created by land theft from Indigenous peoples. Returning to land debt, we argue that institutions need to begin from a perspective of what is owed to Native peoples in their policy decisions. That is, such decisions should take account of the benefits historically accrued by institutions residing on forcibly taken Indigenous land, and then examine how that debt can be repaid by supporting Native students, families, and communities.